2015
DOI: 10.1016/j.mathsocsci.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Conjectural variations in aggregative games: An evolutionary perspective

Abstract: Suppose that in symmetric aggregative games, in which payoffs depend only on a player's strategy and on an aggregate of all players' strategies, players have conjectures about the reaction of the aggregate to marginal changes in their strategy. The players play a conjectural variation equilibrium, which determines their fitness payoffs. The paper shows that only consistent conjectures can be evolutionarily stable in an infinite population, where a conjecture is consistent if it is equal to the marginal change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Previous works noted this connection in simple duopoly models (Dixon and Somma, 2003;Müller and Normann, 2005), in two-player games (Possajennikov, 2009) and in symmetric aggregative games (Possajennikov, 2015). What I add in this paper is that the link between consistent and evolutionarily stable conjectures hold in more general n-player asymmetric situations.…”
Section: Introductionsupporting
confidence: 52%
“…Previous works noted this connection in simple duopoly models (Dixon and Somma, 2003;Müller and Normann, 2005), in two-player games (Possajennikov, 2009) and in symmetric aggregative games (Possajennikov, 2015). What I add in this paper is that the link between consistent and evolutionarily stable conjectures hold in more general n-player asymmetric situations.…”
Section: Introductionsupporting
confidence: 52%
“…However, aggregate-taking behavior may make the crucial difference here, as the interdependent behavioral effects between the players are much more restricted by aggregate-taking behavior. In accordance with this reasoning, Possajennikov [39] demonstrated that only so-called zero conjectures are evolutionarily stable; the latter means that players do not believe that the other players react to their actions.…”
Section: Talent Investmentmentioning
confidence: 82%
“…Possajennikov (2003) defines the aggregate-taking equilibrium of the game, where individual strategies do not affect the aggregate contribution, and proves its stability for games with a finite number of players. In a later work, Possajennikov (2015) considers players' beliefs about the marginal individual contribution to the aggregate strategy to define the dynamics of the game. He proves that only in games with an infinite number of players, consistent conjectures with respect to the NE are evolutionary stable.…”
Section: Introductionmentioning
confidence: 99%